Interações mediadas por compostos orgânicos voláteis entre a soja, o percevejo Euschistus heros (Hemiptera: Pentatomidae) e o parasitoide Telenomus podisi (Hymenoptera: Platygastridae) - Silva, Willian José Rodrigues da (2015)
The plants release volatile organic compounds that can activate the defense in plants, besides interfere in the herbivores behavior and natural enemies. In this study had as objective to evaluate how exposure of soybean plants Glycine max L. (Fabales: Fabaceae) to Volatile Organic Compounds - VOCs synthetic affect the plants, brown stink bug, Euschistus heros (Fabricius, 1794) and the egg parasitoid Telenomus podisi Ashmead (Hymenoptera: Platygastridae). Three different soybean cultivars were tested, defined by preliminary studies, one resistant to aphid, Dowling and two susceptible, BR-16 and Jataí. The plants were sprayed with VOCs (cis)-3-hexenyl acetate, methyl salicylate, (cis)-jasmone and (trans)-2-octen-1-ol. The experiments conducted with plants exposed to VOCs were intended to answer the following assumptions: (i) the soybean plants treated by VOCs have their induced defense; (ii) changes induced by VOCs in the volatile emission affect the attraction of T. Podisi; (iii) plants induced by VOCs affect the development of brown stink bug (E. heros); (iv) exposure to VOCs change in weight of shoot and root of the induced plants; (v) action of plant volatiles induced by the VOCs affect in the parasitoid behavior and bugs in soybean field area. The results showed that the compounds: (cis)-3-hexenyl acetate and methyl salicylate affect the production and release of VOCs mixtures formed by (cis)-3-hexenyl acetate, (trans)-β-ocimene, (trans,trans)-α-farnesene and (trans,trans)-4,8,12-trimethyl-1,3(trans),7(trans),11-tridecatetraene (TMTT), and these volatiles may be responsible for attraction of egg parasitoid T. podisi, and also affect the food by seeking behavior and oviposition sites in addition of the development of brown stink bug E. heros. Plants‟ exposure to VOCs do not interfere in the initial development of the plant. In the field test was verified the parasitoids presence belonging to several families, mainly from Platygastridae family. Although no differences were observed in the bugs abundance. Spraying with (cis)-3-hexenyl acetate and methyl salicylate influence in the tritrophic interaction among induced plants, parasitoid T. podisi and the stik bug E. heros.